2010
DOI: 10.1519/jsc.0b013e3181e72709
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Endurance Field Tests and Match Performance in Young Soccer Players

Abstract: The purpose of this study was to examine the relationship between popular endurance field tests and physical match performance in elite male youth soccer players. Eighteen male young soccer players (age 14.4±0.1 years, height 1.67±4.8 cm, body mass 53.6±1.8 kg) were randomly chosen among a population of elite-level soccer players. Players were observed during international championship games of the corresponding age categories and randomly However the Hoff test was only significantly related with sprint distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
132
5
22

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(175 citation statements)
references
References 32 publications
16
132
5
22
Order By: Relevance
“…Harley et al [5] showed that the distances covered by youth English soccer players ranged from *6,000 m (Under 12) to *7,600 m (Under 16), with high-intensity running ranged from *1,700 to *2,500 m (Under 12 and Under 16, respectively), whereas other studies [6,7] have shown a total distance covered during a match of *700 m by highintensity running and *250 m by sprinting in Italian Under 14 soccer players. In addition, Vaeyens et al [8] have demonstrated better performances of sprint and vertical jump in elite youth soccer players (Under 13-Under 14) when compared with sub-elite and non-elite youth soccer players.…”
Section: Introductionmentioning
confidence: 97%
“…Harley et al [5] showed that the distances covered by youth English soccer players ranged from *6,000 m (Under 12) to *7,600 m (Under 16), with high-intensity running ranged from *1,700 to *2,500 m (Under 12 and Under 16, respectively), whereas other studies [6,7] have shown a total distance covered during a match of *700 m by highintensity running and *250 m by sprinting in Italian Under 14 soccer players. In addition, Vaeyens et al [8] have demonstrated better performances of sprint and vertical jump in elite youth soccer players (Under 13-Under 14) when compared with sub-elite and non-elite youth soccer players.…”
Section: Introductionmentioning
confidence: 97%
“…Besides fitness tests, time-motion analysis of both matches and SSGs in training could perhaps provide additional information about football-specific fitness. Indeed, many studies found positive correlations between aerobic fitness tests and match locomotor performance assessed as (high intensity) distance covered (Buchheit, Mendez-Villanueva, Simpson, & Bourdon, 2010;Castagna, Impellizzeri, Cecchini, Rampinini, & Alvarez, 2009;Castagna, Manzi, Impellizzeri, Weston, & Barbero Alvarez, 2010;Krustrup et al, 2003;Rampinini et al, 2007a;Rebelo, Brito, Seabra, Oliveira, & Krustrup, 2014) or estimated metabolic power (Manzi et al, 2014). However, in team sports, maximal (physical) performance is difficult to define during an actual match (Halson, 2014), as it is influenced by many factors such as player position, score line, opposition and tactics (Carling, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although no other studies related aerobic or anaerobic endurance tests to SSG locomotor performance, previous studies (Buchheit et al, 2010;Castagna et al, 2009;Castagna et al, 2010;Krustrup et al, 2003;Rampinini et al, 2007a;Rebelo et al, 2014) The present study assessed the variability and test-retest reliability of the 6v6-SSG for commonly used time-motion variables, including estimated metabolic power and acceleration metrics. Variability was low for total distance and metabolic power (both 4%), but higher for distance covered above high-intensity thresholds for speed, acceleration and metabolic power (8-14%).…”
mentioning
confidence: 95%
“…Cristian Lizana (3,10,11,22) . Ao mesmo tempo, demanda jogadores com alta capacidade de adaptação a situações novas e imprevisíveis (8,19,27,28) .…”
Section: Autoresunclassified